Pelatihan Da’i Untuk Membangun Keterampilan Public Speaking Santri TK/TPA Di Desa Massila Kecamatan Patimpeng Kabupaten Bone - R. Firdaus Wahyudi (Fakultas Ushuluddin dan Komunikasi Islam, 2025)
Da'wah is a religious duty that requires every Muslim person to play a role in inviting or calling others to the right path. In preaching, it takes courage and confidence to appear in public. Therefore, public speaking skills are very necessary, especially for children who have the desire and courage to appear in public. One way that can be used to build children's public speaking skills is to conduct da'wah training from an early age, including training to deliver lectures. This training was conducted at the kindergarten / TPA in Erabaru village and aims to help develop children's skills to dare to appear in public speaking and train students to foster self-confidence, In this training, the method used is the method of approach and motivation. The approach methods used include observation, socialization, implementation of activities and evaluation. The result of this training is that some students are brave and confident to appear to deliver lectures and try to memorize lecture scripts so that they can be smoother when performing in front of their friends.